2019
DOI: 10.1016/j.ebiom.2019.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 as a therapeutic target for chronic low back pain: Upregulation in human cerebrospinal fluid and pre-clinical validation with chronic reparixin in the SPARC-null mouse model

Abstract: Background: Low back pain (LBP) is the leading global cause of disability and is associated with intervertebral disc degeneration (DD) in some individuals. However, many adults have DD without LBP. Understanding why DD is painful in some and not others may unmask novel therapies for chronic LBP. The objectives of this study were to a) identify factors in human cerebrospinal fluid (CSF) associated with chronic LBP and b) examine their therapeutic utility in a proof-of-concept pre-clinical study. Methods: Pain-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 62 publications
(106 reference statements)
4
44
0
1
Order By: Relevance
“…Moreover, we con rmed that protein expression of SASP factors (NGF, IL-1β, TNF-α and IL-8) was higher in the TLR-2 activated cells. These proteins were chosen since they have been associated to be IVD degeneration and TLR-2 induction and have been reported to be highly expressed in degenerate human and mice IVDs (35,37,38). Taken together our results validate that IVD cells from patients with back pain and IVD degeneration at both gene and protein level respond to TLR-2 activation.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, we con rmed that protein expression of SASP factors (NGF, IL-1β, TNF-α and IL-8) was higher in the TLR-2 activated cells. These proteins were chosen since they have been associated to be IVD degeneration and TLR-2 induction and have been reported to be highly expressed in degenerate human and mice IVDs (35,37,38). Taken together our results validate that IVD cells from patients with back pain and IVD degeneration at both gene and protein level respond to TLR-2 activation.…”
Section: Discussionsupporting
confidence: 69%
“…Activation of neuronal TNF receptors increases the production of IL-1β, IL-6, and CCL2 [formerly known as monocyte chemoattractant protein-1 (MCP-1)]. Both IL-1β and IL-6 have been shown to have activity in acute inflammatory and chronic pain (146)(147)(148). Indeed IL-1β enhanced pain transduction and conduction via modulation of ion channels such as TRP ankyrin 1 (TRPA1), TRPV1, and Nav1.7.…”
Section: Peripheral Nociceptor Terminalmentioning
confidence: 99%
“…IL-8 has also been implicated in conditions such as chronic low back pain (LBP). Krock et al showed a specific upregulation of this chemokine in the cerebrospinal fluid of LBP patients with degenerating disks and a reduction of disk degeneration and chronic back pain in a mouse model (148). In a neuropathic orofacial pain condition, the burning mouth syndrome, patients present an elevated level of plasma IL-8, and this signature directly correlates with pain and depressive symptomatology (150).…”
Section: Peripheral Nociceptor Terminalmentioning
confidence: 99%
“… 27 , 66 Knockout animals lacking IL-1β, IL-1 receptor 1, or MCP-1 demonstrate reduced or abrogated pain behavior in peripheral nerve injury models, and inhibition of IL-8 decreased pain in a rodent chronic low back pain model. 1 , 20 , 54 Attenuation of neuroinflammation, through inhibition of microglial activation, targeting of specific microglial genes, or selective depletion of spinal microglia, relatively consistently reverses pain hypersensitivity. 25 , 35 …”
Section: Introductionmentioning
confidence: 99%